Exchange of phospholipids between low and high density lipoproteins of squirrel monkeys - D. Roger Illingworth; Oscar W. Portman (Journal of Lipid Research, 1972)
Ultracentrifugal analysis of the plasma of squirrel monkeys at various times after the injection of [Me-14C]choline revealed the specific activities of lecithin in both high (HDL) and low (LDL) density lipoproteins to be similar. This was also true for sphingomyelin.The exchange of phospholipids in vitro was studied by incubating unlabeled plasma with labeled LDL and HDL isolated 40 hr after the injection of [Me-14C]choline. Recentrifugation of plasma immediately after the addition of either 14C-labeled LDL or HDL demonstrated that significant exchanges of both lecithin and sphingomyelin had occurred. In further studies, 14C-labeled LDL or HDL were incubated with plasma and the low density lipoproteins were rapidly isolated by precipitation with heparin–Mn2+. Complete equilibration of lecithin and sphingomyelin between LDL and HDL was attained after 4 and 5 hr, respectively. The fractional exchange rates for lecithin and sphingomyelin of LDL to HDL were 0.60 hr–1 and 0.45 hr–1. Corresponding values for HDL to LDL were 0.51 hr–1 and 0.53 hr–1. Inhibition of plasma lecithin:cholesterol acyltransferase reduced the exchange of sphingomyelin but had no effect on lecithin exchange. The rates of exchange of four lecithin subfractions of different unsaturation between LDL and HDL were the same.